Human Dignity in Bioethics. - Dilley, Stephen (Routledge annals of bioethics., 2013)
Human Dignity in Bioethics brings together a collection of essays that rigorously examine the concept of human dignity from its metaphysical foundations to its polemical deployment in bioethical controversies. The volume falls into three parts, beginning with meta-level perspectives and moving to concrete applications. Part 1 analyzes human dignity through a worldview lens, exploring the source and meaning of human dignity from naturalist, postmodernist, Protestant, and Catholic vantages, respectively, letting each side explain and defend its own conception. Part 2 moves fro.